Jiawei Foshou San Induces Apoptosis in Ectopic Endometrium Based on Systems Pharmacology, Molecular Docking, and Experimental Evidence. (27th October 2019) - Wei, Jiahui; Zhao, Binxin; Zhang, Chengling; Shen, Bingbing; Zhang, Ying; Li, Changxi; Chen, Yi
Abstract : Foshou San is a typical gynaecological formula with wild usage in traditional Chinese medicine. Jiawei Foshou San (JFS) is a novel ingredient prescription from Foshou San with antiendometriosis effect in unclear mechanisms. To uncover the potential application and proapoptotic mechanisms of JFS, JFS ingredient-drug target-disease networks, GO enrichment, and pathway analysis were established for potential application prediction. Molecular docking and validation in vivo were investigated by the proapoptotic mechanisms of JFS. In this study, 99 common targets were related to 108 diseases. 484 biological processes, 44 cell components, 59 molecular functions, and 37 pathways were significantly identified in GO enrichment and pathway analysis. In molecular docking, ligustrazine showed binding activity with Bcl-2, Bax, caspase-9, caspase-3, and PARP. In vivo, JFS elevated the shrink rate of ectopic endometrium, by suppressing E2 and PROG. An in-depth study showed that apoptosis was activated through diminishing Bcl-2, rising Bax and Bad, and expressing more caspase-3 and caspase-9 using JFS. JFS promoted the protein level of cleaved-PARP. In brief, JFS might be applied for various diseases through multiple targets and pathways, especially endometriosis by Bcl-2 pathway. These findings reveal the potential application for further evaluation and uncover the proapoptotic mechanism of JFS.